2008
DOI: 10.1590/s0034-70942008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Hipoxemia após revascularização miocárdica: análise dos fatores de risco

Abstract: Older and overweighted patients, those with left ventricular dysfunction, and those who needed CPB presented an increased risk of severe hypoxemia after MR. In those patients, the use of perioperative ventilatory strategies, with elevated positive expiratory pressures and alveolar recruitment maneuver should be considered to prevent postoperative pulmonary dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 17 publications
5
24
0
5
Order By: Relevance
“…In our result, the most frequent postoperative pulmonary complications were pleural effusion and atelectasis, confirming another study that showed pleural effusion frequency of 84% and atelectasis of 65% (8). The frequency of pulmonary complications is high after CAGB, reaching 40%, contributing to patient morbidity and mortality, increased hospitalization times and a rise in hospital costs (23,24).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In our result, the most frequent postoperative pulmonary complications were pleural effusion and atelectasis, confirming another study that showed pleural effusion frequency of 84% and atelectasis of 65% (8). The frequency of pulmonary complications is high after CAGB, reaching 40%, contributing to patient morbidity and mortality, increased hospitalization times and a rise in hospital costs (23,24).…”
Section: Resultssupporting
confidence: 87%
“…The use of CEC and the absence of pulmonary ventilation during this period are also determining factors in the development of pulmonary complications after cardiac surgery, likely due to alterations in the mechanical properties of the respiratory system caused by changes in complacency and pulmonary resistance (7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…CPB is considered the main responsible for lung damage, whereas all patients undergoing CPB suffer some disorder of respiratory function due to various factors such as interstitial edema, pulmonary congestion, damage to the pulmonary vascular endothelium and microatelectasis [8,9,11,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pulmonary complications of patients on the preoperative period can be noted on the 1 st postoperative day and on the 6th postoperative day. A greater number of radiographs changed on the 6 th postoperative day was found (78%) compared to the 1st postoperative day (40%), occurring on intubation, decrease of respiratory complications and thus resulting in reduced length of hospital stay associated with the reduction in hospital costs [5,8,10,20,21].…”
Section: Radiological Findingsmentioning
confidence: 99%
See 1 more Smart Citation